MOTIVASI BELAJAR SISWA PADA PELAJARAN MATEMATIKA MELALUI MEDIA KONKRET KELAS TIGA DI SD NEGERI SENDANGMULYO 02 SEMARANG - Rikha Nafida; Nurani Fadilah; Veryliana Purnamasari (STKIP Subang, 2024)
Mathematics is a subject that makes students accustomed to thinking systematically, scientifically and critically. In learning Mathematics, students often experience difficulties both in understanding the language which is lacking or difficulties in calculating. With the use of concrete learning media, it is hoped that it can provide concrete manifestations in learning material and foster interest, attention and student learning motivation. The purpose of this study is to describe the learning motivation of grade 3 students in Mathematics using concrete learning media at SDN Sendangmulyo 02 Semarang. The method used in this research is qualitative research. Data collection techniques in this study were in the form of observation, questionnaires, and documentation. The results of the study show that through concrete learning media, students' motivation in Mathematics looks very good. The conclusion of this study is that there is very good learning motivation in grade 3 students in Mathematics through concrete media at SDN Sendangmulyo 02 Semarang